Freshwater fishing among Lapita people: The Sleepers (Teleostei: Eleotridae) of Teouma, Vanuatu. (August 2019) - Bouffandeau, Laurie; Béarez, Philippe; Keith, Philippe; Bedford, Stuart; Spriggs, Matthew
Abstract: The study of the ichthyofaunal corpus yielded by the archaeological site of Teouma, Efate Island, Vanuatu, has revealed the unexpected presence of a significant number of bones of Eleotridae (Sleepers) on the site, as early as 2920–2870 cal. B.P. Out of the 8560 identified fish remains associated with the Lapita layers, which document the period of initial settlement of the archipelago, 1368 have been determined as belonging to eleotrids, including species of the genera Giuris, Ophiocara and Eleotris . They represent 16% of the corpus and occupy second place among the dominant families in an assemblage composed otherwise of a wide-range of marine coastal and reef-associated taxa. Even though the Lapita economy is characterised by an intensive and broad-spectrum exploitation of all terrestrial and marine resources available and readily procurable, the eleotrids of Teouma are the first clear evidence thus far of the exploitation of freshwater environments by Lapita communities anywhere in their range. A river and a swamp are present in the vicinity of the site, and hooks and lines and/or multi-pronged spears could have been used. Passive gear such as weirs, fish-traps or nets might have been applied as well, enabling the capture of sleepers in larger quantities. The results presented here offer an original insight of an unknown facet of Lapita subsistence strategies and aim to highlight the antiquity of freshwater fishing at a regional scale. Highlights: Bones of freshwater fish have been identified at the archaeological site of Teouma. The river and the swamp nearby have been exploited by Lapita settlers 3000 years ago. This is the earliest zooarchaeological evidence of freshwater fishing in Melanesia. Eleotridae (Sleepers) occupy second place among the dominant taxa of the assemblage. Lapita people obviously did not neglect any resources from the islands they colonised.